Electrical Properties of Sandwich-like Multilevel Phase Structure BNT-BT Lead-Free Piezoelectric Ceramics. Issue 1 (24th July 2021) - Bai, Chungeng; Wang, Junjun; Lin, Weipeng; Wu, Fengmin; Jiang, Jiuxing
Abstract: Sandwich-like multilayer (BNT-0.05BT, BNT-0.07BT, and BNT-0.09BT) composite ceramics was performed by traditional solid-state reaction method. The results show that the dielectric properties of (Bi1/2Na1/2)TiO3-BaTiO3 (BNT-BT) ceramics were improved significantly from 580 to 1278. By fitting the dielectric constant ɛ r with electric field intensity, the linear relationship conformed to Rayleigh formula, and the dielectric properties of the loops were studied. The results show that the dielectric properties were improved mainly because the intrinsic contribution of structural changes of composite ceramics increased. As the temperature rises, the dielectric response of ceramics to the electric field increases gradually.